Mineralogy, solid-phase fractionation and chemical extraction to assess the mobility and availability of arsenic in an urban environment. (January 2019) - Amaibi, Patrick M.; Entwistle, Jane A.; Kennedy, Nattalie; Cave, Mark; Kemp, Simon J.; Potgieter-Vermaak, Sanja; Dean, John R.
Abstract: A multi-disciplinary approach, using chemical extraction and analytical structural techniques, has been used to assess the mobility and availability of arsenic in urban soil samples from two current housing sites. Arsenic concentrations in each site varied between 126 and 1660 mg/kg (Site A) and 40–24, 900 mg/kg (Site B). Using a non-specific sequential extraction approach, it was possible to identify two distinct, site specific, As-containing fractions i.e. Fe-As-Ca (Site A) and As-Fe (Site B), in the soils. Further investigation using a sequential extraction approach identified the main As component in the reducible fraction, linking As with Fe-oxides in the soils. Further investigation of the crystalline mineral phases, by X-ray diffraction, within the most As-contaminated soils (up to 24, 000 mg/kg) identified no As-bearing minerals but identified the major component as quartz (SiO2 ) with an array of minor and trace minerals. Further mineralogical investigation, using micro-Raman in the major As-contaminated soils (from Site B) as well as re-confirming the presence of the major mineral (quartz) additionally identified the As-bearing minerals pharmacosiderite (KFe4 [(H2 O)4 (AsO4 )3 ].6H2 O) and mimetite (Pb5 (AsO4 )3 Cl) in the trace mineral component, alongside amorphous carbon, chromite (FeCr2 O4 ), goethite (α-FeO(OH)), gypsum (CaSO4 .H2 O), muscovite (KAl2 (AlSi3 O10 )(F, OH)2 ), magnetite (Fe3 O4 ), martite (α-Fe2 O3 ), psilomelane (Ba, H2 O)2 Mn5 O10 ), pyrrhotite (Fe7 S8 ) and rutile (TiO2 ). The identification and presence of several Fe-rich minerals could be considered as the major hosts of As in the soil matrix. It is concluded that while the soil contains elevated levels of As, it's lack of mobility in the soil, means that minimal remedial action is required provided the sites are left undisturbed and free of human endeavour and activity. Highlights: Investigation of arsenic in soil from current residential urban housing sites. Role of sequential extraction methods to evaluate chemical form and mobility. Structural techniques used to identify mineralogy. Role of XRD, Raman and SEM-EDX in soil studies.